INULIN AS A PREBIOTIC AND FAT REPLACER IN MEAT PRODUCTS - Dragan Vasilev; Vesna Djordjević; Nedjeljko Karabasil; Mirjana Dimitrijević; Zoran Petrović; Branko Velebit; Vlado Teodorović (Теория и практика переработки мяса, 2017)
Fat reduction in meat products is demanded by consumers concerninghealth issues but represents a serious challenge for meat industry as fatty tissue plays an important role for the products properties. Because of that, a special attention is paid to the substances that could replace fatty tissue in meat products. Inulin represents a non digestible fructooligosaccharide that on the one hand represents a good prebiotic substance and from the other hand posses such technological propeties that make it a good fat replacer. In  aqueous systems inulin forms a gel having a structure similar to fats, it has neutral taste and smell and have no impact on the aroma of meat products. Inulin could be added to meat products in form of powder as well as a water suspension. Low fat fermented sausages with good sensory quality could be produced with the addition of inulin as a fat replacer, and such products have abit lower pH- and aw-value and contain a higher number of lactic acid bacteria then conventional products. In heat treated sausages, inulin improves water holding capacity and stability of the low fat meat batter, which reduces cooking loss and shows no adverse effect on the sensory properties of the low fat product. But, there are also certain limitations because it should be paid attention to the degree of polymerization as well as the amount of inulin added the product. Otherwise, on the one hand there could be some adverse effectson sensory properties of the product and from the other hand an excessive amount of inulin could lead to digestive problems by consumers.